F110. THE BRIEF NEGATIVE SYMPTOM SCALE (BNSS): VALIDATION IN A MULTICENTER BRAZILIAN STUDY. (1st April 2018) - Medeiros, Heydrich; Elkis, Helio; Vasconcelos, Selene; Martins, Diana; Alexandria, Raissa; Albuquerque, Ana; Freitas, Rosana; Scardoelli, Maria; Sarno, Elaine Di; Napolitano, Isabel; Oliveira, Graça; Vizzotto, Adriana; et al.
Abstract: Background: Negative symptoms are a core feature of schizophrenia. The Brief Negative Symptom Scale (BNSS) is a new scale developed to assess negative symptoms in schizophrenia. Methods: The present study aimed to examine the construct validity of BNSS, by using convergent and divergent validities as well as factor analysis, in a Brazilian sample of 111 outpatients diagnosed with schizophrenia by DSM-5. Patients were evaluated by the Brazilian version of the BNSS and positive and negative subscales of the Positive and Negative Syndrome Scale (PANSS) Results: Assessment of patients by both instruments revealed an either an excellent internal consistency (Cronbach's alpha = 0.938) or inter-rater reliability (ICC = 0.92), as well as a strong correlation between BNSS and negative PANSS (r = 0.866) and a weak correlation of the instrument with the positive PANSS (r = 0.292) thus characterizing adequate convergent and discriminant validities, respectively. The exploratory factor analysis identified two distinct factors, namely, motivation/pleasure and emotional expressivity, accounting for 68.63% of the total variance. Discussion: The study shows that the Brazilian version of the BNSS has adequate psychometric properties and it is a reliable instrument for the assessment of negative symptoms in schizophrenia, either for clinical practice or research.